Validasi Metode Analisis Senyawa Obat Dalam Sampel Biologis (Urine) - Shinta Puspa Dwiyanti; Diva Afiah Hanifa Irawan; Zuyyinna Alya Abbas; Marsah Rahmawati Utami; Lina Nurfadhila (Journal of Pharmaceutical and Sciences, 2023)
Urine is one of the selected specimens because the content of metabolites and drugs in urine is relatively high. In addition, the easiest and most stable sample to examine is a urine sample. The aim of this study was to determine a valid analytical method for analyzing drug compounds in biological samples of urine. The research method used was to conduct a literature study on several credible journals with journal criteria for the last 10 years regarding determining drug levels in human urine. The final results were obtained from five different analytes, namely Trimethoprim (TMP), ciprofloxacin, acetaminophen, methanol, and opiates which have been validated using several validation methods namely; HPLC with Photodiode Array Detector (PDA), HPLC with fluorescence detector, capillary electrophoresis with UV detector, spectrofluorometric, Gas Chromatography-Mass Spectrometry (GC-MS), GC-FID, and Spectro photo densitometry using human samples urine, all have met the validation requirements. So, it can be concluded that the biological sample of human urine is quite accurate as the sample used in the analytical validation method.